Relationship of EMAST and Microsatellite Instability Among Patients with Rectal Cancer - Devaraj, Bikash (Springer-Verlag, 2010)
BACKGROUND: Elevated microsatellite instability at selected tetranucleotide repeats (EMAST) is a genetic signature identified in 60% of sporadic colon cancers and may be linked with heterogeneous expression of the DNA mismatch repair (MMR) protein hMSH3. Unlike microsatellite instability-high (MSI-H) in which hypermethylation of hMLH1 occurs followed by multiple susceptible gene mutations, EMAST may be associated with inflammation and subsequent relaxation of MMR function with the biological consequences not known. We evaluated the prevalence of EMAST and MSI in a population-based cohort of rectal cancers, as EMAST has not been previously determined in rectal cancers. METHODS: We analyzed 147 sporadic cases of rectal cancer using five tetranucleotide microsatellite markers and National-Cancer-Institute-recommended MSI (mononucleotide and dinucleotide) markers. EMAST and MSI determinations were made on analysis of DNA sequences of the polymerase chain reaction products and determined positive if at least two loci were found to have frame-shifted repeats upon comparison between normal and cancer samples from the same patient. We correlated EMAST data with race, gender, and tumor stage and examined the samples for lymphocyte infiltration. RESULTS: Among this cohort of patients with rectal cancer (mean age 62.2 ± 10.3 years, 36% female, 24% African American), 3/147 (2%) showed MSI (three males, two African American) and 49/147 (33%) demonstrated EMAST. Rectal tumors from African Americans were more likely to show EMAST than Caucasians (18/37, 49% vs. 27/104, 26%, p = 0.014) and were associated with advanced stage (18/29, 62% EMAST vs. 18/53, 37%, non-EMAST p = 0.02). There was no association between EMAST and gender. EMAST was more prevalent in rectal tumors that showed peri-tumoral infiltration compared to those without (30/49, 60% EMAST vs. 24/98, 25% non-EMAST, p = 0.0001). CONCLUSIONS: EMAST in rectal cancer is common and MSI is rare. EMAST is associated with African-American race and may be more commonly seen with metastatic disease. The etiology and consequences of EMAST are under investigation, but its association with immune cell infiltration suggests that inflammation may play a role for its development.